(untitled) (Journal of Scientific Research, 2014)
In this study, a Gaussian amp function relating to the Gaussian family is employed to approximate the output intensity profile of various arrangements of air holes in photonic crystal fibers (PCFs) with small d/? values. The studied structures include six distinctive designs starting with square lattice and carried on up to the PCF with Nano configuration. It is shown that d/? = 0.4 is the best value of low d/? ratios (0.2 ? d/? ? 0.4) which leads to the rise of the central intensity noticeably and the reduction of the full width at half maximum at three studied wavelengths (? = 1.35 , 1.55 and 1.65?m). Keywords: Photonic crystal fibers; Central intensity; Gaussian function. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.16901 J. Sci. Res. 6 (2), 193-203 (2014)